2017
DOI: 10.3390/w9030229
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Three Long-Term Gridded Climate Products for Hydro-Climatic Simulations in Tropical River Basins

Abstract: Gridded climate products (GCPs) provide a potential source for representing weather in remote, poor quality or short-term observation regions. The accuracy of three long-term GCPs (Asian Precipitation-Highly-Resolved Observational Data Integration towards Evaluation of Water Resources: APHRODITE, Precipitation Estimation from Remotely Sensed Information using Artificial Neural Network-Climate Data Record: PERSIANN-CDR and National Centers for Environmental Prediction Climate Forecast System Reanalysis: NCEP-CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 88 publications
10
43
0
Order By: Relevance
“…Nonetheless, the probability density functions and cumulative distribution functions show that the estimates are well centered (density peak around 0 and cumulative distribution functions characterized by a well-marked logarithmic shape). Finally, our results are consistent with those of other studies on the validation of PERSIANN-CDR data in other regions of the world [52,54,56] and confirm the interest of testing this dataset to explore potential indices of climate change in the southern Amazon. …”
Section: Quantitative Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…Nonetheless, the probability density functions and cumulative distribution functions show that the estimates are well centered (density peak around 0 and cumulative distribution functions characterized by a well-marked logarithmic shape). Finally, our results are consistent with those of other studies on the validation of PERSIANN-CDR data in other regions of the world [52,54,56] and confirm the interest of testing this dataset to explore potential indices of climate change in the southern Amazon. …”
Section: Quantitative Analysissupporting
confidence: 91%
“…Again in China, Yang et al [53] compared four satellite precipitation products and concluded that the performance of PERSIANN-CDR data is stable over the year, especially because of monthly gauge adjustment. In Malaysia, Tanet al [54] judged the performance of PERSIANN-CDR to be moderate as it appeared to slightly underestimate extreme precipitation events. Concerning the Amazon, comparisons of PERSIANN (which is a different product to PERSIANN-CDR) and rain gauge data are available [23].…”
Section: Persiann-cdr Datamentioning
confidence: 99%
See 1 more Smart Citation
“…24-Tan et al [46] investigated the accuracy of three long-term gridded data records: APHRODITE, PERSIANN-CDR, and NCEP-CFSR. They concluded that the APHRODITE and PERSIANN-CDR data often underestimated extreme precipitation and streamflow, while the NCEP-CFSR data produced dramatic overestimations.…”
Section: Appendix Amentioning
confidence: 99%
“…In addition, the RRI model has been utilized with GSMaP to simulate the 2008 flood event in Pakistan [20]. In the meantime, SRE products have been compared with each other and their characteristics and accuracy have also been evaluated [21][22][23]. However, evaluation among multiple SREs in terms of flood inundation reproducibility has not been done yet.…”
Section: Introductionmentioning
confidence: 99%